2019
DOI: 10.1101/2019.12.11.872457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential contributions of left-hemispheric language regions to basic semantic composition

Abstract: Semantic composition, i.e. the ability to combine single words to form complex meanings, is a core feature of human language. Despite growing interest in the basis of semantic composition, the neural correlates and the interaction of regions within this network remain a matter of debate.In the present fMRI study, we designed a well controlled two-word paradigm in which phrases only differed along the semantic dimension while keeping syntactic information alike. 33 healthy participants listened to meaningful ph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 64 publications
(90 reference statements)
6
22
0
Order By: Relevance
“…Critically, the current study used a task that required participants to activate and contextualize abstract concepts. In this task, we identify the angular gyrus as a critical hub for the dynamic use of abstract knowledge, consistent with the view that this region plays a key role in combinatory linguistic processing (David & Yee, 2019;Graessner et al, 2021;Price et al, 2015;Pylkkänen, 2019Pylkkänen, , 2020. Such combinatory processing may be particularly critical for abstract concepts, which more strongly need to be contextualized in a situational way during everyday use.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Critically, the current study used a task that required participants to activate and contextualize abstract concepts. In this task, we identify the angular gyrus as a critical hub for the dynamic use of abstract knowledge, consistent with the view that this region plays a key role in combinatory linguistic processing (David & Yee, 2019;Graessner et al, 2021;Price et al, 2015;Pylkkänen, 2019Pylkkänen, , 2020. Such combinatory processing may be particularly critical for abstract concepts, which more strongly need to be contextualized in a situational way during everyday use.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings yield multiple key insights into abstract concept representation: First, our findings provide novel evidence for IPC as a core area for concept coding (Binder et al, 2009). Using a task that required participants to activate and contextualize abstract concepts, we identify the angular gyrus as a critical hub for the dynamic use of abstract knowledge, consistent with the view that this region plays a key role in combinatory linguistic processing (Graessner et al, 2021;Price et al, 2015;Pylkkänen, 2019). Such combinatory processing is critical in real-life situations that require applying abstract knowledge in a situational and meaningful way.…”
Section: Discussionsupporting
confidence: 72%
“…More broadly, pMTG is robustly associated with basic phrase comprehension deficits across a large number of studies. Data from brain stimulation implicate postero-middle temporal areas in syntactic processing (Duffau et al, 2014), and another recent red-boat study in fMRI implicated a broad portion of pMTG in meaningful phrase composition (Graessner et al, 2021). Impairments in grammaticality judgments have primarily been linked to posterior temporal lobe damage (Wilson and Saygin, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Functional neuroimaging studies using the red-boat paradigm implicate the left anterior temporal lobe (ATL), specifically the temporal pole (Antonucci et al, 2008;Lambon Ralph et al, 2012;Wilson et al, 2014;Zhang and Pylkkänen, 2018), inferior frontal regions (Graessner et al, 2021b(Graessner et al, , 2021a and posterior temporal regions (Flick and Pylkkänen, 2020;Matchin and Hickok, 2020) as crucial nodes for phrase composition with variations in the timing (180-350ms post-composition) and duration (50-100ms) of their engagement (Kochari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This LATL composition effect is also observed for two-word phrases in written (Baron et al, 2010;Bemis and Pylkkänen, 2011;Westerlund et al, 2015) and auditory (Bemis and Pylkkänen, 2013;Sheng et al, 2019) comprehension cross-linguistically. Several other regions are also thought to contribute to combinatory processing: the LIPL, hypothesized to encode relational aspects of meaning (Boylan et al, 2017;Williams et al, 2017) and composition more generally (Binder and Desai, 2011;Bemis and Pylkkänen, 2013;Price et al, 2015Price et al, , 2016Graessner et al, 2021); the vmPFC, found sensitive to the semantic properties of combinatory expressions (Pylkkänen and McElree, 2007;Bemis and Pylkkänen, 2011;Pylkkänen et al, 2014;Blanco-Elorrieta et al, 2018); and the LIFG, associated with both long-distance dependencies (Stromswold et al, 1996;Leiken et al, 2015) and phrasal composition (Zaccarella and Friederici, 2015). The current study tests, for the first time, whether these regions (LATL, LIPL, vmPFC, LIFG) exhibit composition effects across code switches.…”
Section: Introductionmentioning
confidence: 90%